Developing a critical agenda to understand pro‐environmental actions: contributions from Social Representations and Social Practices Theories. (27th June 2016) - Batel, Susana; Castro, Paula; Devine‐Wright, Patrick; Howarth, Caroline
Abstract : Debates over the value and compatibility of different approaches to understanding and changing environmental‐relevant actions proliferate across the social sciences. This article reviews and discusses some of the (socio‐)psychological and sociological approaches in those debates. We will start by critically reviewing the (socio‐)psychological perspectives, highlighting two main shortcomings. First, they are often partial in their focus—concentrating on the consumption side of climate‐relevant actions and, relatedly in changing these actions at the individual level. They tend to assume that individual change equates to social change and, with that, fail to contextualize 'anti'‐environmental actions in current neoliberal, capitalist societies. Second, they usually present the mainstream (socio‐)psychological approaches, which are ontologically individualistic and cognitive, as the only existent ones, therefore neglecting other perspectives within Social Psychology which might actually be (more) compatible with sociological perspectives. We then suggest that Social Representations Theory (SRT), as an ontologically social‐psychological approach and a theory of social change, might be reconciled with sociological approaches, such as Social Practices Theory (SPT), in contrast to the more individualistic (socio‐)psychological perspectives. After reviewing the main tenets of SRT, its discrepancies and potential synergies with SPT, we discuss how both can be articulated to understand different stages of the social change process toward more environmentally sustainable societies. While SPT might be more suitable to understand stability or how some actions become habitual, SRT might be better equipped to understand how those change, or how individuals and groups negotiate new actions with old ones. WIREs Clim Change 2016, 7:727–745. doi: 10.1002/wcc.417 This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Behavior Change and Responses